Let me tell you about healthy ageing and about my quality of life: listening to the baby boomer voice. (28th June 2018) - Hardy, Margaret; Oprescu, Florin; Millear, Prue; Summers, Mathew
Abstract : Purpose: The purpose of this paper is to determine how baby boomers define healthy ageing and quality of life, and if late life university study could have a beneficial impact for future health-promoting initiatives. Design/methodology/approach: Qualitative data were collected from Australian baby boomers. Data were inductively categorised to identify and report emergent themes. Findings: The majority of respondents believed healthy ageing meant being mentally and physically active, with later life university study contributing to mental health, which improves their quality of life. Social implications: Later life university study can have positive health outcomes for baby boomers and may contribute to the quality of their life. Originality/value: This study suggests that baby boomers are quite clear about how they define healthy ageing and quality of life: maintaining good health and retaining their independence. Some baby boomers stated that intellectual stimulation was critical for their overall health and wellbeing. Baby boomers identified as belonging to this group engagement in an educational (i.e. university) programme could be considered as a health-promoting intervention.